THE DIFFERENCE BETWEEN NEUTROFIL TOTAL, NEUTROPHIL / LYMPHOCYTE AND PLATELETS / LYMPHOCYTE RATIO IN NORMAL PATIENTS, NSTEMI, STEMI - Elisabeth Setianingrum; Purwanto A P (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Acute Coronary Syndrome (ACS) is a Non-ST-Elevation Myocardial Infarct (NSTEMI) and ST-Elevation Myocardial Infarct (STEMI) caused by atherosclerosis vascular, endothelial dysfunction as an acute inflammatory response. Absolute Neutrophils (AN), Neutrophil/Lymphocyte Ratio (NLR), and Platelet/Lymphocyte Ratio (PLR) is a systemic inflammation marker in inflammatory diseases. The research purpose was to compare AN, NLR, and PLR as an inflammatory marker in normal patients and, NSTEMI, STEMI. A cross-sectional observational study of 101 ACS patients at the Dr. Kariadi Hospital, divided into three groups (normal, NSTEMI, and STEMI). Neutrophil and lymphocyte were counted manually. Leukocyte and platelet value were determined by hematology analyzer. Data were analyzed with the Kruskal-Wallis test followed by post hoc Mann-Whitney. There was a difference in AN, NLR value between STEMI and NSTEMI compared to normal patients. There was no significant difference between PLR value.